A stable solution of linear programming problems with the approximate matrix of coefficients - Erokhin, Vladimir (2017 Constructive Nonsmooth Analysis and Related Topics (dedicated to the memory of V.F. Demyanov) (CNSA), 2017)
A.N. Tikhonov's approximate system of linear algebraic equations solution approach is extended to find a stable solution of a linear programming problem with an approximation of the coefficient matrix. This approach is formalized as the special case of a linear programming problem. Necessary and sufficient conditions for the existence of the solution of specified problem and the form of this solution are studied. Numerical example of the improper linear programming problem with an approximation of the coefficient matrix solution is shown.